Gender Segregation and Income Differences in Nicaragua. Issue 3 (3rd July 2019) - Herrera, Carlos; Dijkstra, Geske; Ruben, Ruerd
ABSTRACT: Despite having higher average education levels, Nicaraguan women still earn much less than men. Furthermore, the country has one of the highest levels of occupational gender segregation in Latin America. This paper aims to explain the gender income gap in Nicaragua, taking into account individual characteristics, engagement in specific occupations and sectors, and geographical location. Using a multilevel framework, the study finds that while a considerable part of the income gap can be explained by women's employment in occupations and sectors with low remuneration, another substantial part of this gap is attributable to the prevalence of patriarchal gender norms – and thus cannot be explained by human capital factors. These results show that understanding labor market segregation is vital for comprehending the perseverance of the gender income gap, and they further imply that women's progress in breaching the gender stereotypes in Nicaragua is still limited.